Smart Pothole Detection and Mapping System - Borgalli, Rohan (Journal of Ubiquitous Computing and Communication Technologies, 2020)
In any country public services and infrastructure is very crucial part of development. The qualities of these are shed light on how well the government is doing its job, the consequences of disparities in local funding. But there are few answers on these many questions. This is why this system was implemented to detect all types of potholes using different methods based on data acquired by ultrasonic sensor, gyroscope and image acquired by Pi-camera which gives the intensity and shape of the pothole in any given condition. Potholes have been a major problem in Mumbai road in recent times. Proposes system is trying to study potholes and their distribution on the roads of Mumbai with the help of hardware mentioned to acquire images and deep learning framework for potholes detection and mapping then using Android App and Google map it is generalize to the entire city.
Keywords: pothole; detection; mapping; Internet of Things(IoT); image processing; deep learning